Uji Alat Augmentasi dan Konservasi Parasitoid Telur Kepik Hijau (Nezara viridula L.) pada Tanaman Kedelai (Glycine max L.) - Zulfa Nuril Hikmah; Hari Purnomo (Fakultas Pertanian Universitas Jember, 2020)
Soybean pod damage caused by N. viridula reached 61.37% of the total pods and 61.67% of the total seeds attacked. Efforts were made, namely the application of chemical insecticides made from active chlorpyrifos which can reduce the population of N. viridula to reach 57.4% and the insecticides made from deltamerin which are reducing the population by 51.6%. Control is needed that can reduce the negative effects caused by chemical insecticides, one of which is mechanical control. Mechanical control can be done one of them with augmentation and conservation tools. the research is by taking the eggs of N. viridula in the field and laying the eggs in an augmentation and conservation tool with several treatments of different filter cloth diameters, 0.1 mm; 0.3 mm; 0.2 mm; and 0.6 mm. Observations were made by looking at and counting the number of parasitoids that were able to pass through the filter cloth and those that did not pass through the filter cloth, followed by identification of the species of the parasitoid that was obtained. The results showed that the parasitoids were able to escape in all treatments but with varying amounts. The difference in number can be influenced by the presence of parasitoids in the field and the level of parasitoid parasitation. Likewise with Trichogramma sp also able to pass on all treatments. Therefore, the most suitable treatment is treatment with a 0.1 mm diameter filter cloth. The identified parasites were T. rowani and T. podisi